An investment analysis of planting sweet cherries in Washington - Rattray, Michael (Kansas State University, 2017)
Choosing a viable long-run crop investment can be risky and time consuming for farmers. The high establishment costs and risk for perennial tree crops like cherries require producers to conduct careful analysis prior to investing. Farmers must not only look to prices today but to the long term price trends that are likely affect the investment profitability. This thesis is an investment analysis on planting twenty-five acres of Sweetheart cherries in Washington State. The purpose is to calculate the total net present value over the commercially productive life of the cherry trees. Prices received by growers for sweet cherry production can fluctuate. Sweet cherries are also susceptible to yield volatility. Therefore, a sensitivity analysis was calculated that shows the changes in price and yield and its effect on net present value. Sweet cherry production for fresh market is also labor intensive. Changes in labor supply and minimum wage can affect a farmers profit margins. This thesis evaluates the risk of a wage shock to the total net present value of the investment. The net present value calculated was found to be positive, making planting Sweetheart cherries a viable option for Hillslide Orchards. The internal rate of return was favorable at 12.30% return. Yield risk was relatively low in this model showing positive net present values at 60% over base yield and still positive at 40% below base yields. The price risk was found to be slightly higher with negative net present values below $1.00 or 20% below the base price. It is important to note that this model represents planting a block of Sweetheart cherries within an existing operation. There are additional costs that would be incurred for other farm operations, not modeled here that could decrease the overall profitability under alternative planting scenarios.
Keywords: Cherries; Agriculture economics; Business Plan; Orchard; Washington State